Freedom and Restriction of Opinion and Expression in Modern Indonesian Poem Seen from Levinson’s Pragmatics - Irsyadi, Achmad Naufal; Anoegrajekti, Novi; Kusumayanti, Dina Dyah; Dzulqarnain, M. Iskandar (Universitas Negeri Semarang, 2021)
We revisited Wiji Thukul’s poetry from normative and constructivist theories to find the scope of freedom and restriction of opinion and expression through various forms of literary works. We applied stylistic perspective of Jeffries and McIntyre (2010) by involving three of Wiji Thukul's poems, namely Aku Menuntut Perubahan, Sajak Suara, and Puisi Sikap. In their stylistic concept, Jeffries and McIntyre (2010) also have a tendency towards the fields of Pragmatics and Sociolinguistics which emphasized more on speech. Levinson’s Pragmatic approach (1983) connected pragmatics with human aspects, namely psychology, biology, and sociology that were inherent in sign. Therefore, as a symbol (sign) in a literary work, every word and speech were identical and closely related to these three aspects. We perceived that the choice of words in WIji Thukul's poetry aimed to create a threat to the power by the New Order, carried out a protest against the policies and actions of the New Order, made an allusion about the power of the New Order, and denigrated and isolated the New Order. Thus, Wiji Thukul's poetry was a combination and communication between psychological and biological aspects of the author as well as the sociology of society.